A Meta-Analytic Review of Moral Disengagement and Cyberbullying - Zhao, Lijun; Yu, Junjian (Frontiers in Psychology, 2021)
With the development of technology, cyberbullying prevalence rates are increasing worldwide, and a growing body of literature has begun to document cyberbullying behavior. Moral disengagement is often considered a key correlate factor in cyberbullying (Gini et al., 2014; Kowalski et al., 2014; Zych et al., 2019). This article aims to conduct a meta-analysis review of the relationship between moral disengagement and cyberbullying and some psychosocial and cultural variables. Based on the PRISMA method, a random-effects meta-analysis is employed in this study to obtain reliable estimates of effect sizes and examine a range of moderators (age, gender, measure method, and cultural background). Relevant studies, published from 2005 to February 30, 2021, were identified through a systematic search of the Web of Science, ScienceDirect, SpringerLink, Pubmed, EBSCO, and Wiley Online Library. Finally, 38 studies (N=38425) met the inclusion criteria. The meta-analysis conclusion demonstrated that moral disengagement positively correlated medium intensity with cyberbullying (r=0.341). Age, gender, and cultural background had moderated the relationship between moral disengagement and cyberbullying.